Board Characteristics and Financial Performance of Listed Insurance Companies in Nigeria - Timothy Aondona Aondover; Kayode Oluwafemi Ishola (Britain International for Academic Research (BIAR) Publisher, 2026)
This study examined the impact of board characteristics on the financial performance of listed insurance companies in Nigeria. Specifically, it investigated the effect of board size and board gender diversity on Net Profit Margin (NPM) and Return on Assets (ROA). The study was anchored on Agency Theory and adopted an ex-post facto research design. Secondary data were obtained from the audited annual reports of 16 insurance companies listed on the Nigerian Exchange Group (NGX) over the period 2015–2024. Data were analysed using descriptive statistics, Pearson correlation, and panel regression techniques, with company size and company age included as control variables. The findings revealed that board size had no significant effect on Net Profit Margin but exerted a significant positive effect on Return on Assets, indicating that an optimal board size enhances asset utilization and overall firm performance. In contrast, board gender diversity had no significant effect on either Net Profit Margin or Return on Assets. The study concluded that board size is a critical corporate governance mechanism for improving the financial performance of listed insurance companies in Nigeria, whereas board gender diversity has not yet translated into measurable profitability gains. The study recommends that insurance companies maintain an optimal board size that promotes effective monitoring, strategic decision-making, and accountability. It also recommends that regulatory authorities strengthen corporate governance practices by ensuring merit-based board appointments capable of enhancing firm performance.